Tracheal inflammatory myofibroblastic tumor presenting as an obstructive pediatric foreign body. Issue 12 (2nd December 2022) - Liu, Alice Q.; Kotadia, Naima; Tobia, Amjad; Rayment, Jonathan H.; Whyte, Simon; Felton, Mark
Abstract: We describe an unusual presentation of a suspected pediatric foreign body (FB) aspiration which was found to be an occlusive inflammatory myofibroblastic tumor (IMT) of the distal trachea. These are rarely reported entities, with the potential for significant airway bleeds. Multidisciplinary discussion and involvement allowed for a safe patient outcome. Abstract : Pediatric foreign body aspirations are common presentations to emergency departments. However, while rare, tumors or other masses may have a similar presentation and should be considered on the differential.